2010
DOI: 10.3802/jgo.2010.21.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of the class I homeobox genes in ovarian carcinoma

Abstract: Objective: Although some sporadic reports reveal the link between the homeobox (HOX) genes and ovarian carcinoma, there is no comprehensive analysis of the expression pattern of the class I homeobox genes in ovarian carcinoma that determines the candidate genes involved in ovarian carcinogenesis. Methods: The different patterns of expression of 36 HOX genes were analyzed, including 4 ovarian cancer cell lines and 4 normal ovarian tissues. Using a reverse transcription-polymerase chain reaction (RT-PCR) and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
15
1
1
Order By: Relevance
“…Slightly different results were found in a more recent study by Hong et al (2010) [16]. In this study the expression of 36 HOX genes in ovarian cancer cell lines and tissues were compared to normal ovarian tissue, revealing a difference in expression of 11 HOX genes ( HOXA7 , B3 , B4 , B6 , C10 , C11 , D1 , D3 , D10 , D11 and D13 ).…”
Section: Introductioncontrasting
confidence: 58%
“…Slightly different results were found in a more recent study by Hong et al (2010) [16]. In this study the expression of 36 HOX genes in ovarian cancer cell lines and tissues were compared to normal ovarian tissue, revealing a difference in expression of 11 HOX genes ( HOXA7 , B3 , B4 , B6 , C10 , C11 , D1 , D3 , D10 , D11 and D13 ).…”
Section: Introductioncontrasting
confidence: 58%
“…We found that 9 out of the 10 HOXB genes were upregulated, the most significant being HOXB4 , B5 , B7 and B13 . HOXB4 upregulation has been shown to be associated with the development of platinum resistance in cell lines, and its over‐expression in ovarian cancer has been reported previously in a relatively small study using only 4 cell lines and 7 ovarian cancer tumour samples, but no oncogenic function for this gene has been proven. HOXB4 has been implicated as a cancer‐related gene in other malignancies, including breast cancer, leukaemia and lung canceR .…”
Section: Discussionmentioning
confidence: 86%
“…These cell lines were maintained in minimal essential medium (Life Technologies, Inc, Grand Island, NY) supplemented with 10% fetal bovine serum and 100 Kg/mL of streptomycin. Cell lines were maintained in a humidified 5% CO 2 incubator at 37-C. 20 Establishment of Paclitaxel-Resistant EOC Cells SKOV3 cells were washed thoroughly with phosphatebuffered saline (PBS) and then transferred to RPMI-1640 medium containing 10% fetal bovine serum and 100 Kg/mL of streptomycin. The cells were continuously exposed to increasing doses of paclitaxel for more than 6 months, during which time the medium was replaced every 3 days.…”
Section: Ovarian Cancer Cell Lines and Culturementioning
confidence: 99%